The Poetics of Language in the Algerian Sufi Novel: The Novel “Bayāḍ al-Yaqīn” by Abdelkader Amich as a Model - rebiai, khadidja; boulkaibet, naima (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : This study inspects the narrative language niceties in Algerian Sufi novel by using Abdelkader Ammich’s novel"whiteness of certitude " as a sample which presents the intellectual muslim who survives self-loneliness and dominated by violence and exclusion of globalisation and technological superiority, what pushes his soul to look for serenity in the narrator’s trip through the Sufi language to the spiritual shining world. This research aims to reveal the different levels of language poetry and the artistic features in the novel, using the Sufi text with Intertextuality process.